Questioning the Validity of the New York Convention 1958 on Recognition and Enforcement of Foreign Arbitral Awards in Indonesia - Roosdiono, Anangga W.; Taqwa, Muhamad Dzadit (Universitas Negeri Semarang, 2024)
This article questions the legal validity of the New York Convention of 1958 (